Sonar Observation of Heat Flux of Diffuse Hydrothermal Flows. Issue 10 (14th October 2022) - Jackson, Darrell; Bemis, Karen; Xu, Guangyu; Ivakin, Anatoliy
Abstract: Previous work using multibeam sonar to map diffuse hydrothermal flows is extended to estimate the heat output of diffuse flows. In the first step toward inversion, temperature statistics are obtained from sonar data and compared to thermistor data in order to set the value of an empirical constant. Finally, a simple model is used to obtain heat‐flux density from sonar‐derived temperature statistics. The method is applied to data from the Cabled Observatory Vent Imaging Sonar (COVIS) deployed on the Ocean Observatories Initiative's Regional Cabled Array at the ASHES vent field on Axial Seamount. Inversion results are presented as maps of heat‐flux density in MW/m 2 and as time series of heat‐flux density averaged over COVIS' field of view. Plain Language Summary: Hydrothermal activity in the deep ocean is an important component of the processes that cool the Earth. This activity is of two types: venting of hot, turbid water in "black smokers" and diffuse venting of warm, mostly clear water. It has proven difficult to measure the heat output of diffuse venting, as the usual temperature‐measuring devices only provide data at a few points, and further, do not give the velocity of the flow as needed to determine the amount of heat being delivered to the ocean. The Cabled Observatory Vent Imaging Sonar (COVIS) has been used to measure heat flowing from an area of 500 square meters in the caldera of Axial Seamount. COVIS was installed in July 2018 on the Ocean Observatories Initiative Regional Cabled Array, which allows shore‐based investigators immediate access to COVIS data. It is hoped that COVIS will continue to monitor heat flow long enough to see the effects of an eruption of Axial volcano. Key Points: Multibeam sonar is used to observe heat flux of diffuse hydrothermal flows The inversion method estimates vertically averaged temperature fluctuation Validation and calibration of method by direct measurement is needed